Rhabdomyolysis in Indonesian marathon athlete (Faculty of Medicine Universitas Indonesia, 2003)
Serum and urine myoglobin assessments were conducted on 37 national marathon athletes who participated in the Asian Marathon III & Proklamaton XV. Three athletes showed a myoglobin value of < 50 ug/L and the other 34 athletes showed a myoglobin value of 211-3300 ug/L. Rhabdomyolysis were only found in 2 athletes, thus the prevalence of rhabdomyolysis is 6.1%. A correlation was found between myoglobinemia value and the athleteâs performance. (Med J Indones 2003; 12: 207-14)